No Regard for Those Who Need It: The Moderating Role of Follower Self-Esteem in the Relationship Between Leader Psychopathy and Leader Self-Serving Behavior - Barelds, Dick P. H.; Wisse, Barbara; Sanders, Stacey; Laurijssen, L. Maxim (Frontiers in Psychology, 2018)
Recent instances of corporate misconduct and examples of blatant leader self-serving behavior have rekindled interest in leader personality traits as antecedents of negative leader behavior. The current research builds upon that work, and examines the relationship between leader psychopathy and leader self-serving behavior. Moreover, we investigate whether follower self-esteem affects the occurrence of self-serving behavior in leaders with psychopathic tendencies. We predict that self-serving behaviors by psychopathic leaders are more likely to occur in the interaction with followers low in self-esteem. We first conducted an experimental study (N = 156), in which we manipulated follower self-esteem, measured leader psychopathy, and assessed their combined effect on leader self-serving behavior using an ultimatum game. We then conducted a multi-source field study (N = 124 leader-follower dyads) using questionnaires to assess leader psychopathy, follower self-esteem, and perceived leader self-serving behavior. Across both studies, we found that leader psychopathy was positively related to their self-serving behavior, but only when followers had low rather than high self-esteem. As expected, our studies showed that the degree to which (perceived) psychopathic traits of leaders are reflected in their behavior depends on the characteristics of their followers. Apparently, the behavioral expression of negative leader traits is not only a matter of the trait strength, but instead is the result of the interplay between leader and follower in a certain context.